Experimental and computational characterization of carbon fibre based structural battery electrode laminae. (22nd March 2022) - Carlstedt, David; Rittweger, Florian; Runesson, Kenneth; Navarro-Suárez, Adriana M.; Xu, Johanna; Duan, Shanghong; Larsson, Fredrik; Riemschneider, Karl-Ragmar; Asp, Leif E.
Abstract: In this paper, electrode laminae consisting of carbon fibres embedded in structural battery electrolyte (CF-SBE electrodes) are characterized with respect to their multifunctional (i.e. combined electrochemical and mechanical) performance utilizing experimental and numerical techniques. The studied material is made from commercially available polyacrylonitrile (PAN)-based carbon fibres and a porous SBE matrix/electrolyte, which is composed of two continuous phases: a solid polymer skeleton (vinyl ester-based) and a Li-salt containing liquid electrolyte. Experimental and numerical studies are performed on CF-SBE electrode half-cells, whereby a coupled electro-chemo-mechanical finite element model is exploited. Results show that, similar to traditional batteries, electrode thickness, transport properties of the electrolyte and applied current significantly affect electrochemical performance. For example, increasing the electrode thickness of the studied CF-SBE electrode from 50  μ m to 200  μ m results in a reduction in specific capacity of approximately 70/95% for an applied current of 30/120 mA g −1 of fibres, respectively. Further, Li-insertion induced longitudinal expansion of carbon fibre electrodes are video microscopically recorded during charge/discharge conditions. In liquid electrolyte the total/reversible longitudinal expansion are found to be 0.85/0.8% while for the CF-SBE electrode the reversible expansion is found to be 0.6%. The fibre expansion in the CF-SBE electrode gives rise to residual strains which is demonstrated numerically. We expect that the utilized computational framework and experimental data open a route to develop high-performing, both mechanically and electrochemically, carbon fibre based battery electrode laminae for future lightweight structural components with energy storage ability. Graphical abstract: Image 1 Highlights: Carbon fibre electrodes embedded in structural battery electrolyte are studied experimentally and theoretically. Effects of electrode lamina thickness on electrochemical performance are measured. Li-insertion induced longitudinal expansion of carbon fibre electrodes is measured in situ during electrochemical cycling. A previously developed coupled electro-chemo-mechanical finite element model is validated based on experimental data.